2023
DOI: 10.3390/ijfs11010025
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Income Generation: The Role of Staff Participation and Awareness

Abstract: The policy of educational autonomy through legal entity state universities is a very interesting issue. Universities have the authority to manage finances and collect additional income, specifically generated income. Its successful implementation also provides more significant income to everyone in the institution through greater incentives, thereby helping to improve the economic conditions of staff, institutions, and all academics. This study examines the empirical evidence of factors influencing university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Using a structural equation model and survey data from 111 respondents across various units, faculties, and universities. Mahmud et al [32] examined the influence of staff awareness, staff participation, and top management support on income generation. They found that staff awareness affects income-generating performance indirectly through top management support.…”
Section: Financial Sustainability In Higher Education Institutions (H...mentioning
confidence: 99%
“…Using a structural equation model and survey data from 111 respondents across various units, faculties, and universities. Mahmud et al [32] examined the influence of staff awareness, staff participation, and top management support on income generation. They found that staff awareness affects income-generating performance indirectly through top management support.…”
Section: Financial Sustainability In Higher Education Institutions (H...mentioning
confidence: 99%
“…Other studies have found that universities that can diversify sources of income through income-generating activities will make their financial condition viable (Irvine and Ryan, 2019) so that MIG accountability will run according to organizational goals (Siswanto et al, 2013). Universities can carry out various kinds of financial innovations so that they are not dependent on funds provided by the central government (Jyothi and Rathod, 2019;Mahmud et al, 2023). Strategic partnerships are carried out with outside parties such as research grants, assisting the project, developing the business unit and partnerships with private institutions to increase FV in order to improve revenue management performance (Swift, 2012;Harun et al, 2019).…”
Section: Financial Viabilitymentioning
confidence: 99%
“…This law also guarantees the autonomy of higher education institutions with a legal entity, the state's obligation to finance higher education and access to people who come from economically disadvantaged circles. With full autonomy, tertiary institutions can independently manage their own households in accordance with campus vision, mission and goals of the campus (Cahyana and Farida, 2019; Mahmud et al ., 2023). Thus, universities can develop and innovate more quickly.…”
Section: Introductionmentioning
confidence: 99%
“…The CSR program is implemented based on Law Number 40 of 2007 concerning Limited Liability Companies which is implemented through Government Regulation Number 47 of 2012 concerning the Social and environmental responsibility of limited liability companies.Participation of all parties is an important key in empowering community socio-economic institutions from CSR programs to formulate, agree on and implement programs from the surrounding community, companies that have programs, and local governments that have policies.Participation is a process of growing awareness of interrelationships among stakeholders in society, namely social groups and communities by adopting policies and other institutions. Then participatory development is a process that involves community activities in all substantial decisions relating to people's lives [4][5][6][7] The development paradigm is currently experiencing a shift, where development emphasizes empowerment, which is known as people-centered development, resource-based development, and institutional development. Community empowerment can be interpreted as a process that builds people or society through developing community capabilities, changing people's behavior, and community organizing.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the basic problems that need attention are the problem of the lack of involvement of implementers at the operational level, the problem of implementation coordination between units, and the problem of adequate budget for programs to increase local food crop production. (6) Policies in the field of food security are only assessed as physical development, by providing material assistance that is only of temporary benefit. It is necessary to examine the problems that always arise, namely socio-cultural factors, and pay attention to the local wisdom of the community as development capital.…”
Section: Introductionmentioning
confidence: 99%